2010
DOI: 10.1016/j.joca.2010.06.007
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of osteoclasts prevents cartilage loss and pain in a rat model of degenerative joint disease

Abstract: Subchondral bone remodeling plays an important role in nociception and the pathobiology of the MIA model with osteoclasts being implicated in both bone and cartilage resorption. Inhibition of osteoclastic activity when initiated early leads to improved efficacy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
120
0
6

Year Published

2012
2012
2019
2019

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 115 publications
(134 citation statements)
references
References 49 publications
8
120
0
6
Order By: Relevance
“…This aggravates the degenerative process, resulting in irreversible physical damage to cartilage, and gradually involves the whole joint with increase in the severity of OA (29). Besides this, inflammation attracts immune cells and osteoclast precursors, thereby increasing osteoclast formation and bone resorption in subchondral region (32). Various studies have shown that proinflammatory cytokines affect survival and phenotype of chondrocytes in several ways.…”
Section: Discussionmentioning
confidence: 99%
“…This aggravates the degenerative process, resulting in irreversible physical damage to cartilage, and gradually involves the whole joint with increase in the severity of OA (29). Besides this, inflammation attracts immune cells and osteoclast precursors, thereby increasing osteoclast formation and bone resorption in subchondral region (32). Various studies have shown that proinflammatory cytokines affect survival and phenotype of chondrocytes in several ways.…”
Section: Discussionmentioning
confidence: 99%
“…Changes in weightbearing asymmetry were evaluated one day before and once a week after OA induction. The percentage of weight placed on the right hind limb was determined using the formula below [28] .…”
Section: Pain Behavior Testingmentioning
confidence: 99%
“…Several groups of investigators have demonstrated that bisphosphonates show promise for cartilage preservation to a degree [4,17,18]. A recent preclinical study demonstrated that ‘pre-emptive chronic’ bisphosphonate treatment increased bone mineral density (BMD) and was chondroprotective in rat models of joint degeneration.…”
Section: Introductionmentioning
confidence: 99%